Towards implementing scalable and reconfigurable SCADA security testbed in power system environment - Saif Qassim Q.; Jamil N.; Daud M.; Che Hasan H. (Inderscience Publishers, 2023)
Electric power transmission networks; SCADA systems; Security of data; Testbeds; Critical infrastructure systems; Cyber security; Cybersecurity exercise; Industrial control systems; Protection and security; SCADA; Security countermeasures; Unintended consequences; Electric power system security